Study of anatomical variants at osteomeatal complex in cases of chronic maxillary sinusitis - Pathak, Aditya; Yadav, Ramanand (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: To study the contribution of anatomical variations at osteomeatal complex area in development of chronic maxillary sinusitis. Methods: 60 patients with chronic maxillary sinusitis, clinically diagnosed on the criteria layed by Lanza and Kennedy and radiologically supported by X-ray PNS, were included in the study. Nasal endoscopy with different angled endoscopes done under local anaesthesia to recognize the anatomical variants at osteomeatal complex area. Results: In 41.09% of cases anatomical variants like concha bullosa, paradoxical middle turbinate, large bulla ethmoidalis or medially bent uncinate process were detected, but in rest 59.91% of cases of maxillary sinusitis there was no anatomical abnormality. Conclusions: Among the causative factors for development of chronic maxillary sinusitis different anatomical variants at osteomeatal area causes narrowing of the drainage pathway of maxillary sinus leading to development of chronic inflammation of the maxillary sinus.